2022
DOI: 10.3390/cancers14133237
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-Related Gene Expression in Circulating Tumor Cells from Patients with Early Stage Non-Small Cell Lung Cancer

Abstract: Purpose: Metabolic reprogramming is now characterized as one of the core hallmarks of cancer, and it has already been shown that the altered genomic profile of metabolically rewired cancer cells can give valuable information. In this study, we quantified three Metabolism-Related Gene (MRG) transcripts in the circulating tumor cells (CTCs) of early stage NSCLC patients and evaluated their associations with epithelial and EMT markers. Experimental Design: We first developed and analytically validated highly sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The metabolic activity of CTCs has been investigated in several studies and high metabolic activity was associated with poor clinical outcome for colorectal cancer patients [30] and advanced tumor stage and metastasis in prostate cancer [31]. On the other hand, these studies also show that a large proportion of CTCs harbor no or reduced signs of metabolic activity: Chen et al did not detect markers for glucose metabolism in 53.5% of prostate cancer CTCs [31]; Zafeiriadou et al observed an overexpression of the metabolic markers monocarboxylate‐transporter 1, hexokinase 2, or phosphoglycerate dehydrogenase in only 30% or less of non‐small cell lung cancer CTCs [32]. Of note, in our study, the presence of transcripts for certain housekeeping genes such as the metabolism related gene GAPDH could clearly separate cells based on the quality of the RNA sequencing data supporting the effect of metabolism on RNA quality of CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic activity of CTCs has been investigated in several studies and high metabolic activity was associated with poor clinical outcome for colorectal cancer patients [30] and advanced tumor stage and metastasis in prostate cancer [31]. On the other hand, these studies also show that a large proportion of CTCs harbor no or reduced signs of metabolic activity: Chen et al did not detect markers for glucose metabolism in 53.5% of prostate cancer CTCs [31]; Zafeiriadou et al observed an overexpression of the metabolic markers monocarboxylate‐transporter 1, hexokinase 2, or phosphoglycerate dehydrogenase in only 30% or less of non‐small cell lung cancer CTCs [32]. Of note, in our study, the presence of transcripts for certain housekeeping genes such as the metabolism related gene GAPDH could clearly separate cells based on the quality of the RNA sequencing data supporting the effect of metabolism on RNA quality of CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, non-small cell lung carcinoma (NSCL) and malignant melanoma share poor prognosis, and the therapeutic options are few and characterized by scarce effectiveness and resistance [ 39 , 40 ]. These malignancies show a predisposition to EMT and EndMT [ 41 , 42 , 43 , 44 ]. Few are the reports on the development of NO donors in these tumor types [ 18 , 45 , 46 , 47 , 48 ]; thus, the field merits investigation.…”
Section: Introductionmentioning
confidence: 99%